Metaheuristic Optimization of Temporary Facility Layouts in Large-Scale Dam Projects - Ashouri Moridani, Mohammad Hossein; Asadollahfardi, Gholamreza; Lork , Alireza (Management Strategies and Engineering Sciences, 2027)
This study develops a novel Genetic Algorithm (GA)-based framework for multi-objective optimization of workshop layouts in dam construction projects, explicitly addressing curved dam geometry, crane operational constraints, and differentiated safety requirements. The proposed approach employs a hierarchical penalty mechanism to enforce constraint feasibility and a three-phase optimization strategy combining global exploration and adaptive genetic operators to improve convergence and solution quality.The framework is validated through a real-world case study of the Divarsh Rudbar Dam in Iran, optimizing the placement of worker accommodation, cement silos, and material storage facilities. The optimized layout achieves a 21% reduction in transportation distance while satisfying all safety and operational constraints. Sensitivity analysis demonstrates the robustness of the solution under variations in safety parameters.The results highlight the effectiveness of the proposed method as a practical decision-support tool and its capability to address highly constrained, real-world engineering optimization problems.